2014
DOI: 10.1177/0218492314538035
|View full text |Cite
|
Sign up to set email alerts
|

Delayed presentation of aortoesophageal fistula after endovascular repair

Abstract: The incidence of aortoesophageal fistula after thoracic endovascular aortic repair has increased following an increase in thoracic endovascular aortic procedures. A 68-year-old man was diagnosed with aortoesophageal fistula 6 years after thoracic endovascular aortic repair of a descending aortic aneurysm. Due to massive hematemesis and instability, he underwent a left thoracotomy, graft repair of the aorta with stent removal, gastrostomy, and proximal esophagostomy. Unfortunately, he died 1 week later due to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Different mechanisms of AEF development following TEVAR have been postulated including direct erosion of the stent graft into the esophagus, pressure necrosis of the self-expanding prosthesis, ischemic necrosis of the esophagus due to interruption of its vasculature, infection of the stent graft, and the presence of an endoleak [5, 6]. AEF usually occurs within few months after TEVAR, but Kouritas et al [7] reported one case of AEF that developed 6 years after TEVAR.…”
Section: Discussionmentioning
confidence: 99%
“…Different mechanisms of AEF development following TEVAR have been postulated including direct erosion of the stent graft into the esophagus, pressure necrosis of the self-expanding prosthesis, ischemic necrosis of the esophagus due to interruption of its vasculature, infection of the stent graft, and the presence of an endoleak [5, 6]. AEF usually occurs within few months after TEVAR, but Kouritas et al [7] reported one case of AEF that developed 6 years after TEVAR.…”
Section: Discussionmentioning
confidence: 99%
“…While most cases seem to occur within 1-16 months after the TEVAR procedure, Kouritas et al reported one case of AEF that developed 6 years after TEVAR [38]. Other less frequent presentations of post-TEVAR AEF were dysphagia due to extra-luminal compression of the esophageal wall or highgrade fever due to mediastinitis, infection of the surgical/ endovascular graft or sepsis [22,34,35].…”
Section: Symptom Of Post-tevar Aefmentioning
confidence: 99%